The impact of COVID-19 Pandemic on Poverty Levels in Central Java: A Comparative Analysis - Nazah, Nawalin; Winarni, Dwi; Dewandaru, Rhis Ogie (EKOMABIS: Jurnal Ekonomi Manajemen Bisnis, 2024)
This study investigates how poverty levels in Central Java, Indonesia, were affected before, during, and after the COVID-19 pandemic. Initially, there was a gradual decline in poverty rates due to economic growth and poverty alleviation programs. However, the pandemic brought unprecedented challenges, leading to economic disruptions, job losses, and increased vulnerability. Using data from 2017 to 2023 across 29 regencies and 6 cities in Central Java, the research assesses the pandemic's impact on poverty. Factors such as unemployment, education, and minimum wage are examined, with COVID-19 represented by dummy variables. The findings reveal a rise in poverty during and after the pandemic, despite efforts to alleviate it. Education and minimum wage play significant roles in poverty reduction, while unemployment's impact is less clear. The study utilizes statistical models to analyze the data, identifying a random effect model as the most suitable. Heteroscedasticity is addressed using FGLS models, reaffirming the significant impact of variables on poverty. Additionally, the study evaluates Central Java's post-pandemic recovery efforts, providing insights for future policymaking to build resilient and inclusive societies in the face of similar crises.